Promete healthy lifestyles among nursing students - Carvalhais, Maribel (2020)
Background: When entering the University, less healthy behaviors can begin, which can extend to other phases of life, leading to a lower quality of life. Objectives: To identify the lifestyles of nursing students; recognize factors that hinder or facilitate healthy lifestyles; identify ways to promote and raise awareness of healthy lifestyle practices. Methodology: We adopted the “photovoice” methodology, a participatory (qualitative) method, being applied in two Higher Education Institutions in the central region. The sample involved 16 students aged between 18 and 28 years. Results: Most students include in their lifestyle: intensive study, lack of time, unhealthy eating and poor balance between professional / personal and school life. The factors that facilitate healthy lifestyles are the media, while those that make it difficult are the lack of time and resources, advertising and influences. Conclusion: The previous data reflect the urgent need to act in the acquisition of healthy lifestyles. It is essential that higher education institutions often resort to a lifestyle, learning and working environment that promotes the development of their students' health.